Windthrows promote higher diversity of saproxylic beetles (Coleoptera: Passalidae) in a Central Amazon forest - Alencar, Janderson Batista Rodrigues; Fonseca, Claudio Ruy Vasconcelos; Marra, Daniel Magnabosco; Baccaro, Fabrício Beggiato (Insect conservation and diversity, 2022)
Natural disturbances change environmental conditions that play an important role in controlling biodiversity. Large‐scale windthrows (i.e. snapped and uprooted trees) promoted by convective systems cause severe tree mortality and can alter the dynamics of several insect taxons in forests. We assessed the effect of large‐scale windthrows resulting from a squall line event in January 2005 on strictly saproxylic beetle assemblages in Central Amazonia. Using a paired sampling design comparing windthrown and old‐growth forest, we investigated the responses of different metrics of Passalidae diversity (richness, abundance and composition). We found a higher richness and abundance of species in windthrown areas compared with old‐growth forest, and a correlation between species composition and the tree mortality gradient. Differences in the richness and composition of the Passalidae assemblage between disturbed and old‐growth forest suggest that the tree mortality gradient created by windthrows promotes the diversity of saproxylic beetles in Central Amazonia. The direct comparison of large‐scale windthrows in Amazon rainforest showed that Passalidae abundance and richness are favoured in disturbed areas. We also show that the assemblage composition seems to follow the disturbance gradient created by windthrows. Our research contributes novel information on how natural disturbances affect the diversity and demography of saproxylic insects in tropical forests.